2017
DOI: 10.22159/ajpcr.2017.v10i10.20287
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antioxidant and Cytotoxic Activities of Areca Nut (Areca Catechu Linn.) Extract in Human Oral Squamous Cell Carcinoma and Keratinocyte Cells

Abstract: Objectives: Areca (betel, Areca catechu) nuts have been reported to show high contents of phenolic and flavonoid compounds with associated antioxidant activity. This study was undertaken to assess the anticancer potential of areca nut extract on human squamous carcinoma (HSC)-3, HSC-2, and human keratinocyte (HaCat) cancer cell lines, and to elucidate the mechanism of its action. Methods:In this study, the areca nut extract was prepared in 96% ethanol and analyzed for the total phenolic and flavonoid content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This study is a novel or first study which clearly reveals the potential cytotoxicity effect and mechanism of action of areca nut in oral squamous cell lines. Our preliminary study showed that the areca nut has a high content of total phenolic and flavonoid compounds, and showed cytotoxicity activity against HSC-2 and HSC-3 cells 38 . In the present study, we found that areca nut extract can induce apoptosis in HSC-2 and HSC-3 cells with optimum time after 48 hours exposure.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This study is a novel or first study which clearly reveals the potential cytotoxicity effect and mechanism of action of areca nut in oral squamous cell lines. Our preliminary study showed that the areca nut has a high content of total phenolic and flavonoid compounds, and showed cytotoxicity activity against HSC-2 and HSC-3 cells 38 . In the present study, we found that areca nut extract can induce apoptosis in HSC-2 and HSC-3 cells with optimum time after 48 hours exposure.…”
Section: Discussionmentioning
confidence: 80%
“…The pellet was homogenized by pipetting, and the resuspended cells with the culture medium were ready to be used for experiment and cell counting with a hemocytometer. We had performed the cell viability assay previously to evaluate the percentage cytotoxicity and IC 50 of areca nut extract after treating the HSC-2 cells for 72 hours is 629.50 µg/mL while in HSC-3 cells is 164.06 µg/mL 38 . The protocol was approved by the Ethics Committee of the Faculty of Medicine, University of Indonesia no.…”
Section: Methodsmentioning
confidence: 99%